Can cooperative membership foster compliance with New European Union regulations on deforestation-free production? Evidence from cocoa farmers in Western Côte d'Ivoire - Hamza Moluh Njoya; Sofía Cristóbal Reyes; Koumbo Alberic Hien; Franziska Ollendorf; Bonna Antoinette Tokou; Constant Yves Adou Yao; Stefan Sieber; Katharina Löhr (Trees, Forests and People)
Cocoa cultivation (Theobroma cacao) in Côte d'Ivoire faces significant challenges, including deforestation, poverty, and child labour. Like other countries involved in the production and export of palm oil, cattle, soy, coffee, cocoa, timber, and rubber, Côte d'Ivoire now faces the challenge of meeting new European Union regulations on deforestation-free production (EUDR) by June 2025, posing multiple questions and challenges on implementation. While agricultural cooperatives play a vital role in disseminating information, building skills, and enhancing farming practices, their impact on EUDR awareness is underexplored. This study examines the effect of cooperative membership on awareness of the new EUDR among cocoa farmers. We applied a mixed-methods approach combining Propensity Score Matching (PSM) and Inverse Probability Weighting with Regression Adjustment Estimator based on a 2024 household survey (N = 218 households) and 12 focus group discussions (N = 144) involving cooperative and non-cooperative cocoa farmers in the central-west and western regions of Côte d'Ivoire. Descriptive statistics reveal significant differences between the two groups of farmers in terms of demographic and socioeconomic characteristics. Cooperative members are predominantly male, older, and more educated compared to non-cooperative members, with larger households and bigger farms. They also have better access to credit, extension services, and training resources, leading to higher cocoa yields. PSM analysis reveals that cooperative members exhibited higher awareness of EUDR requirements, with results consistent across different matching methods and robust to potential hidden biases, suggesting a possible association between membership and access to EUDR-related information. While the findings indicate a strong association between cooperative membership and EUDR awareness, further research is needed to examine whether this awareness translates into actual changes in compliance behavior. These findings underscore the important role cooperatives can play in enhancing awareness of sustainability regulations like the EUDR and inform policy initiatives aimed at strengthening cooperative participation.